Adherence of Neisseria meningitidis to human epithelial cells. - Salit, I E (1981)
Carrier strains of Neisseria meningitidis are recovered almost solely from the posterior pharynx and they are often nongroupable or rough. Invasive strains can be serogrouped (encapsulated). We studied adherence of both carrier- and patient-derived serogroupable and nongroupable meningococci to buccal epithelial and posterior pharyngeal cells. Fresh meningococcal isolates attached significantly better to pharyngeal than to buccal cells (P = 0.01). Strains that could be serogrouped adhered less than nongroupable strains (P less than 0.05). Meningococci passed in vitro became hemagglutinin negative and nonpiliated. Hemagglutinin-negative meningococci always adhered less to both epithelial cell types than the hemagglutinin-positive variants of the same strain. These results indicate that meningococcal pili probably mediate attachment to oropharyngeal cells, but encapsulation may reduce adherence. Localization of meningococci in the posterior pharynx is in part explained by the receptivity of the epithelial cells in this area for meningococci.